Geriatric nutritional risk index as a predictor for postoperative complications in patients with solid cancers: a meta-analysis - Liu, Weichen; Li, Ming; Lian, Siqin; Hou, Xijie; Ling, Ying (Frontiers in Oncology, 2024)
Background: The geriatric nutritional risk index (GNRI) has been wildly used to predict the prognosis of patients with solid cancer, but it’s value in postoperative complications remains unclear. The aim of our study was to systematically explore the value of the GNRI in postoperative complications in patients with solid cancer. Method: The study conducted a systematic literature search using electronic databases to investigate the influence of the GNRI on postoperative complications in patients with solid cancer. The search covered articles published up until May 2023. The odds ratio (OR) with a 95% confidence interval (CI) was employed to assess the effect of GNRI on postoperative complications. Result: A total of 11 studies with 11,002 patients were enrolled in our meta-analysis. The results suggested that patients with a low GNRI have a higher risk of experiencing postoperative complications (OR=2.51, 95%CI 2.05–3.02, z=9.86, p<0.001) , a higher risk of suffering Clavien-Dindo (CD) grades≥2 complications(OR=2.24, 95%CI 1.84–2.73, z=8.01, p<0.001), a higher risk of suffering infection (OR=1.85, 95%CI 1.18–2.88, z=2.70, p=0.007) and a higher risk of suffering respiratory complications(OR = 2.94, 95%CI: 1.56-5.55, z=3.31, p=0.001). Conclusion: Based on existing evidence, the GNRI was a valuable predictor of postoperative complications in patients with solid cancer.